Sensitivity of Self-Reported Human Papillomavirus Vaccination History Among 18- to 26-Year-Old Men Who Have Sex With Men: Seattle, WA, 2016 to 2018. Issue 1 (23rd January 2022) - Forward, Terra; Meites, Elissa; Lin, John; Hughes, James P.; Unger, Elizabeth R.; Markowitz, Lauri E.; Golden, Matthew; Swanson, Fred; Faestel, Paul M.; Winer, Rachel L.
Abstract : In a study of 18-to-26-year-old men who have sex with men with a documented history of human papillomavirus vaccination, most participants correctly self-reported having received ≥1 dose, but 30% of fully vaccinated participants misreported number of doses. Abstract : Background: We assessed the sensitivity of self-reported human papillomavirus (HPV) vaccination among young adult men who have sex with men (MSM) with documented HPV vaccination. Methods: During 2016–2018, MSM and transgender women aged 18 to 26 years were enrolled in Seattle, WA. A history of HPV vaccination was assessed via self-administered survey, clinic electronic medical records, and the Washington State Immunization Information System. We assessed self-report sensitivity among participants with documented prior HPV vaccination (≥1 dose) in either the electronic medical record or the Washington State Immunization Information System, and used logistic regression to compare sensitivity by age, number of doses, and time since first dose. Results: Of 292 participants with ≥1 documented HPV vaccine dose, 243 self-reported ≥1 dose (sensitivity, 83.2%; 95% confidence interval [CI], 78.4%–87.3%). Compared with participants whose first dose was <1 year ago, the likelihood of self-report was lower among those with ≥3 years since first dose (adjusted odds ratio [aOR], 0.2; 95% CI, 0.1–0.5). Furthermore, compared with participants with only 1 documented HPV vaccine dose, the likelihood of self-reporting ≥1 dose was higher among those with 2 (aOR, 2.4; 95% CI, 1.0–5.5) or ≥3 doses (aOR, 6.2; 95% CI, 2.7–14.4). Among 115 participants with ≥3 documented doses, sensitivity for recalling ≥3 doses was 69.6% (95% CI, 60.3%–77.8%). Conclusions: Most young adult MSM with a documented history of HPV vaccination self-reported prior HPV vaccination. Although recall was highest in those with ≥3 doses, 30% of this fully vaccinated subgroup did not correctly recall the number of doses received, highlighting limitations of self-reporting. Furthermore, results indicating reduced recall with ≥3 years since first dose suggest that sensitivity of self-report among young adult MSM may decline over time as adolescent vaccination coverage increases.